Educational Human Resource Management in Enhancing Teachers’ Professional Competence - Hermuna; Nur Izatul Yazidah; Efa Herlina Batubara; Evi Muliani; Cindy Audia Safira Putri; Robiatul Adawiyah; Catur Prida Retnivia; Laili Komariyah; Yudo Dwiyono (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the implementation of educational human resource management (HRM) and its role in enhancing teachers’ professional competence in schools. In the current era of educational transformation, effective HRM is essential to ensure that teachers continuously develop their professional capacities in line with institutional goals and technological advancement. The research employed a descriptive qualitative approach, involving principals, teachers, and supervisors from five public schools in City Samarinda. Data were collected through in-depth interviews, field observations, and document analysis, and were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that educational HRM contributes significantly to teacher professionalism through three primary dimensions: 1. systematic career planning and competency-based professional development, 2. continuous training, mentoring, and academic supervision, and 3. transparent and fair performance evaluation and reward systems. Supporting factors include visionary and participatory leadership, collaborative organizational culture, and policy support from educational authorities. However, budget constraints, insufficient training facilities, and low teacher motivation remain as barriers to optimal HRM implementation. The study concludes that strengthening integrated, adaptive, and data-driven HRM practices particularly those aligned with digital transformation is crucial to fostering teachers’ professional competence and enhancing educational quality. Educational HRM should not be viewed merely as an administrative function but as a strategic and transformational framework for building a professional, innovative, and sustainable learning environment in the twenty-first century.